Optimization of Local Government Information Systems through Digital Governance - I Made Wirawan (Asian Digital Governance Problems, 2025)
Purpose: This study examines the optimization of local government information systems through digital governance in Denpasar City and explores how digital transformation improves public service delivery, transparency, and citizen participation. Subjects and Methods: The research employed a qualitative descriptive approach using in-depth interviews, direct observations, and document analysis involving government officials, IT staff, and community representatives. Data were analyzed thematically to identify implementation patterns, challenges, and best practices in digital governance. Results: The findings show that integrated digital platforms have improved administrative efficiency, reduced bureaucratic complexity, and strengthened institutional responsiveness. Digital complaint systems, online licensing services, and open data initiatives increased transparency and citizen engagement. However, several socio-technical challenges remain, including limited digital literacy, infrastructural disparities, organizational resistance, and cybersecurity concerns. Adaptive implementation strategies, collaborative governance, and digital literacy programs were identified as important supporting factors for sustainable transformation. Conclusions: Digital governance in Denpasar functions as a continuous institutional and societal transformation process that requires technological integration, organizational adaptation, and inclusive governance strategies to ensure effective and sustainable public service innovation.